Teliosporas de Thecaphora frezii en semillas de maní (Arachis hypogaea) - Pérez, Ignacio Agustin; Asinari, Florencia; Monguillot, Joaquín Humberto; Mortigliengo, S.; Paredes, Juan Andrés; Rago, Alejandro Mario (Asociación Argentina de Fitopatólogos, 2021)
Poster